2019
DOI: 10.7554/elife.47625
|View full text |Cite
|
Sign up to set email alerts
|

An autoregulatory cell cycle timer integrates growth and specification in chick wing digit development

Abstract: A fundamental question is how proliferation and growth are timed during embryogenesis. Although it has been suggested that the cell cycle could be a timer, the underlying mechanisms remain elusive. Here we describe a cell cycle timer that operates in Sonic hedgehog (Shh)-expressing polarising region cells of the chick wing bud. Our data are consistent with Shh signalling stimulating polarising region cell proliferation via Cyclin D2, and then inhibiting proliferation via a Bmp2-p27kip1 pathway. When Shh signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 66 publications
0
23
1
Order By: Relevance
“…However, the molecular mechanisms activated downstream of Hh signalling in the control of cell cycle progression may be cell type-specific. In neural stem cells, Hhmediated cell cycle effects involved the cyclin D-associated kinase, cdk6 (Beukelaers et al, 2011), whereas Hh regulates cell cycle timing through cyclin D2 and p27 Kip1 in the limb (Pickering et al, 2019). In MuSCs, Hh signalling controlled the expression of genes implicated in DNA replication and DNA damage repair, both processes tightly linked to cell cycle checkpoints and cell cycle progression (Lemmens and Lindqvist, 2019).…”
Section: Levels Of Hedgehog Signalling Are Critical For Musc Cell Cycmentioning
confidence: 99%
“…However, the molecular mechanisms activated downstream of Hh signalling in the control of cell cycle progression may be cell type-specific. In neural stem cells, Hhmediated cell cycle effects involved the cyclin D-associated kinase, cdk6 (Beukelaers et al, 2011), whereas Hh regulates cell cycle timing through cyclin D2 and p27 Kip1 in the limb (Pickering et al, 2019). In MuSCs, Hh signalling controlled the expression of genes implicated in DNA replication and DNA damage repair, both processes tightly linked to cell cycle checkpoints and cell cycle progression (Lemmens and Lindqvist, 2019).…”
Section: Levels Of Hedgehog Signalling Are Critical For Musc Cell Cycmentioning
confidence: 99%
“…Thus, the manipulation of Bmp signalling (application of recombinant Bmp2 protein or Nog-expressing cells), following the transient application of a Shhsoaked bead at the anterior margin of the chick wing bud, is capable of changing digit identity in the duplicated patterns (Drossopoulou et al, 2000). Furthermore, the pharmacological inhibition of Shh signalling in the chick wing causes digit 2 to become the mostposterior digit of the pattern, but the application of recombinant Bmp2 protein transforms this digit to a posterior digit 3 (Pickering et al, 2019). However, it is unclear whether promotion of anteroposterior positional values involves the duration/concentration of Shh signalling being interpreted into graded Bmp2 signalling.…”
Section: Antero-posterior Specificationmentioning
confidence: 99%
“…Another role for Shh signalling in the control of proliferation has been uncovered in the chick wing. Grafting experiments showed that the duration of Shh expression and proliferation in the chick wing polarising region are controlled by an autoregulatory intrinsic timing mechanism, which is triggered by the depletion of RA signalling from the trunk of the embryo (Chinnaiya et al, 2014;Pickering et al, 2019) (Fig. 6A).…”
Section: Digit Number Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced cell survival due to Shh inhibition in these experiments may also impact late-stage digit morphogenesis (phalanx formation). Notably, some chick studies have also suggested a role for relay mechanisms in Shh signaling; in particular, a membrane-tethered Shh ligand could still induce posterior digit formation at a distance 3 , and several papers have implicated Bmps as secondary signals modulating digit identity downstream of Shh 2,47,51 . The discrepancy between mouse and chick remains to be explored.…”
Section: Shh Is Required Indirectly To Specify Digit 1 (Thumb)mentioning
confidence: 99%